2007
DOI: 10.1590/s1516-31802007000500003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of supervised physiotherapeutic pelvic floor exercises for treating female stress urinary incontinence

Abstract: CONTEXT AND OBJECTIVE: Urinary incontinence is a public health problem that affects more than 200 million people worldwide. Stress incontinence is the most prevalent type. Pelvic floor muscle exercises have been used for treating it, although there is no consensus regarding their application. The aim of this study was to compare the results from treating female stress urinary incontinence with pelvic floor muscle exercises with or without physiotherapist supervision. DESIGN AND SETTING: This was a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
87
0
30

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 16 publications
3
87
0
30
Order By: Relevance
“…Urinary incontinence (UI) affects over 200 million people worldwide and is considered a public health problem 1 . It is classified as stress UI (SUI) if there is involuntary loss of urine when coughing or sneezing; urge UI (UUI) if there is an abrupt and sudden urge to urinate that cannot be postponed; or mixed UI (MUI) if it is associated with both situations mentioned above, which may also result from emotional aspects 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary incontinence (UI) affects over 200 million people worldwide and is considered a public health problem 1 . It is classified as stress UI (SUI) if there is involuntary loss of urine when coughing or sneezing; urge UI (UUI) if there is an abrupt and sudden urge to urinate that cannot be postponed; or mixed UI (MUI) if it is associated with both situations mentioned above, which may also result from emotional aspects 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The factors involved in the pathophysiology of UI include the following: extra-abdominal pressure on the bladder neck, the presence of a short urethra, decreased estrogen and injury of the sphincter mechanism, pudendal nerve, fascia and pelvic floor muscles (PFM) 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary approaches as well as new effective therapies are very welcome. In a randomized, controlled trial it was demonstrated that exercises directed to pelvic floor muscles, electrical stimulation, and vaginal cones are effective treatments for women with urodynamic stress urinary incontinence 36,37 .…”
Section: Non-cardiac Surgerymentioning
confidence: 99%
“…About one third of adult women have Urinary Incontinence (1)(2) (UI), which can impair a woman's physical, sexual, domestic, and professional and leisure activities (2)(3)(4) . Pregnancy, vaginal delivery, parity, duration of the second stage of labor, difficulty in fetal extraction during a cesarean section, newborn's weight, perineal trauma and other mechanical, endocrinal and neural factors can lead to reduction or loss of the pelvic floor muscle tone causing genitourinary disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) . Altered PFMS has been the focus of studies and research due to the evolution of equipment and exams that make its evaluation and prognosis more precise (10) .…”
Section: Introductionmentioning
confidence: 99%